2022
DOI: 10.3390/cells11060987
|View full text |Cite
|
Sign up to set email alerts
|

Key Genes and Biochemical Networks in Various Brain Regions Affected in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the most complicated progressive neurodegenerative brain disorders, affecting millions of people around the world. Ageing remains one of the strongest risk factors associated with the disease and the increasing trend of the ageing population globally has significantly increased the pressure on healthcare systems worldwide. The pathogenesis of AD is being extensively investigated, yet several unknown key components remain. Therefore, we aimed to extract new knowledge from exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 74 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…The balance between neural excitation and inhibition is essential for proper brain function, and its disruption contributes to neuronal disorders like AD ( 70, 71 ). Dysregulation of the GABAergic synapse pathway and decreased levels of GABA found in this study have also been reported in Alzheimer’s brain ( 72 ). Overall, our findings in the SARS-CoV-2 infected hamster brains indicate the presence of multiple molecular markers associated with the development of neurodegenerative disorders.…”
Section: Discussionsupporting
confidence: 86%
“…The balance between neural excitation and inhibition is essential for proper brain function, and its disruption contributes to neuronal disorders like AD ( 70, 71 ). Dysregulation of the GABAergic synapse pathway and decreased levels of GABA found in this study have also been reported in Alzheimer’s brain ( 72 ). Overall, our findings in the SARS-CoV-2 infected hamster brains indicate the presence of multiple molecular markers associated with the development of neurodegenerative disorders.…”
Section: Discussionsupporting
confidence: 86%
“…Retrograde eCB signaling is one of the major altered pathways in several neurodegenerative diseases such as AD, PD, and MS [ 34 , 35 , 36 ]. Recently a meta‐analysis on transcriptomics datasets from five brain regions of AD patients including hippocampus, CB, temporal cortex, entorhinal, and FC highlighted retrograde eCB signaling as a key altered pathway in AD patients [ 37 ]. Retrograde signaling is the main mechanism by which eCBs regulate short‐ and long‐term forms of plasticity at both excitatory and inhibitory synapses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[16]. Recently, Stefanik et al found that hippocampal expression of miR-34a-5p was sexdependent [24]. MiR-34a-5p is abundantly expressed in the brain and emerging evidence support its involvement in different neurodegenerative diseases as Alzheimer's disease and PD [13].…”
Section: Discussionmentioning
confidence: 99%